Functional Model of Commutative Operator Systems - Zolotarev, V. A. (Журнал математичної фізики, аналізу, геометрії, 2008)
A functional model for a commutative system of the linear bounded operators {T_1, T_2}, when T_1 is a contraction, is built. The construction of functional model is based on an analogue with many parameters of the Lax - Phillips scattering scheme for the isometric dilation U(n) of the semigroup with two parameters T(n)=T_1^n_1T_2^n_2 , where n=(n_1,n_2)Z^2_+. Mathematics Subject Classification: 47A45.